Fishers' Perceptions of the Recurrence of Dynamite-Fishing Practices on the Coast of Tanzania - Katikiro, Robert E.; Mahenge, Jairos J. (Frontiers in Marine Science, 2016)
Dynamite or blast fishing remains the most pervasive destructive fishing method in the coastal waters of Tanzania. It constitutes a major threat to small-scale fisheries through degradation of reefs and other critical habitats for fish. The Tanzanian Government has implemented several measures including a high rate of patrols and surveillance campaigns in the sea to try to deter the use of dynamite in fishing. However, most of these measures have failed to reduce its occurrence over the past years. Little is known on why existing management measures are failing to generate effective solutions to address dynamite and other forms of destructive fishing activities. This study was undertaken to examine perceptions of fishers on the persistent recurrence of dynamite-fishing activities within the present fisheries’ management regulations. A random sample of 180 individual fishers was interviewed in two coastal districts using a household survey questionnaire. Key informants, semi-structured interviews and participant observations were used to collect additional data. Almost two thirds of survey respondents felt that an apparent recurrence of dynamite fishing is attributed to the inconsistencies of the fisheries management approaches deployed to thwart the use of dynamite. However, other factors such as absence of appropriate organisation of the many involved actors, kinship ties and migrant fishers played crucial role on the persistence of dynamite fishing. There was a common perception among all survey participants that lack of trust and transparency towards and within anti-dynamite initiatives negatively impacted the involvement of fishers in their efforts to reduce the use of dynamite. An improved situation where decision-making processes are coordinated among fishers, non-governmental and governmental stakeholders is important to support ongoing management measures, in order to increase legitimacy and long-term success of efforts to get rid of destructive fishing practices among small-scale fishers in Tanzania.